Evaluación de software para Entidades de Certificación [Software evaluation for Certification Authorities] - Villalba Villalba, Tany; Iparraguirre Villanueva, Orlando Clemente (Ventana Informática, 2014)
Abstract There are several software solutions for managing digital certificates, and be use by Certification Authority, so it is useful to identify software with maximum functionality, and extended to be suitable, and thus achieve full functionality of an entity. This software can be free or owner but, for better control and problematic, it is suggested that free and open source, so that adjustments can be made to suit the specific regulations, in this case Peruvian law code. In the analysis of this type of software, standardization criteria (RFC 3647), scalability, ease of maintenance and support from company or user community are used. From the comparison between solutions, we conclude that EJBCA is the most comprehensive, as well as the ease of adaptation. Keywords: digital certificate, certification authority, free software